KONSEP SWASEMBADA PANGAN PERSPEKTIF SURAH AL-NAHL AYAT 11 DALAM TAFSIR AL-MISBAH KARYA M. QURAISH SHIHAB - Wawan Kurniawan; Mohammad Fattah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2026)
This study examines the concept of food self-sufficiency in the Qur’an through an analysis of QS. al-Nahl/16:11 based on Tafsir Al-Mishbah by M. Quraish Shihab. The study is motivated by the growing urgency of food security amid contemporary global challenges, including rapid population growth, climate change, agricultural land conversion, and dependence on food imports. Within the context of Muslim societies, food self-sufficiency is not merely perceived as an economic and developmental issue, but also as a theological, moral, and ethical responsibility associated with humanity’s role as khalifah (vicegerent) on earth. This research aims to analyze the Qur’anic concept of food self-sufficiency, to explore M. Quraish Shihab’s interpretation of QS. al-Nahl/16:11, and to examine its relevance to the development of agricultural technology and contemporary food security efforts. The study employs a qualitative method with a library research approach. Primary data are derived from Tafsir Al-Mishbah, while secondary sources include scholarly books, academic journals, and other relevant literature. Data were collected through documentation techniques and analyzed using content analysis and descriptive-analytical methods. The findings reveal that QS. al-Nahl/16:11 emphasizes the integral relationship between divine grace, natural mechanisms, and human responsibility in managing food resources. M. Quraish Shihab’s interpretation highlights the importance of tafakkur (reflective contemplation), the utilization of knowledge, and the advancement of agricultural technology in a productive, sustainable, and ecologically balanced manner. Consequently, the Qur’anic concept of food self-sufficiency transcends mere production independence and instead underscores the integration of divine values, scientific knowledge, and technological innovation as a pathway toward equitable and spiritually meaningful food security.